The applicability of POSSUM and P-POSSUM scores as predictors of morbidity and mortality in colorectal surgery - CARVALHO-E-CARVALHO,MARIA EMÍLIA (2018)
ABSTRACT Objective: to apply the POSSUM and P-POSSUM scores as a tool to predict morbidity and mortality in colorectal surgery. Methods: we conducted a prospective cohort study of 551 patients submitted to colorectal surgery in a colorectal surgery tertiary referral hospital in Brazil. We grouped patients into pre-established risk categories for comparison between expected and observed morbidity and mortality rates by the POSSUM and P-POSSUM scores. Results: in the POSSUM morbidity analysis, the overall expected morbidity was significantly higher than that observed (39.2% vs. 15.6%). The same occurred with patients grouped in categories II (28.9% x 10.5) and III (64.6% x 24.5%). In category I, the expected and observed morbidities were similar (13.7% x 9.1%). Regarding the evaluation of mortality, it was statistically higher than that observed in category III patients and in the total number of patients (11.3% vs. 5.6%). In categories I and II, we observed the same pattern of category III, but without statistical significance. When evaluating mortality by the P-POSSUM score, the overall expected and observed mortality was similar (5.8% x 5.6%). Of the 31 patients who died, 20.2% underwent emergency procedures and sepsis was the main cause of death. Conclusion: the P-POSSUM score was an accurate tool to predict mortality and could be safely used in this population profile, unlike the POSSUM score.